Direct synthesis of H2O2 from H-2 andO(2) and decomposition/hydrogenation of H2O2 in an aqueous acidic medium over halide-modified Pd/Al(2)O3 catalysts - Samanta, Chanchal; Choudhary, Vasant R. (Applied Catalysis A-General, 2007)
Direct synthesis Of H2O2 from its elements was carried out in an acidic aqueous reaction medium over halide-modified oxidized and reduced Pd/ Al2O3 catalysts under very mild conditions (at 27 degrees C and atmospheric pressure). The halide ions were introduced into the catalyst by incorporating halide ions into supported Pd/gamma-Al2O3 catalyst or via depositing halide ions on the support (gamma-Al2O3) prior to Pd deposition. The H2O2 decomposition and hydrogenation over the corresponding catalysts were also carried out under the reaction conditions similar to those employed for the H2O2 synthesis in order to elucidate the factors strongly affecting the H2O2 yield/selectivity in the direct H2O2 process. The performance of halide-modified Pd/Al2O3 catalysts in the direct H2O2 synthesis revealed that halide insertion in the catalyst system prior to or after Pd deposition on the support had comparable qualitative effect on the H2O2 formation. Both the Pd oxidation state and the nature of the halide ions had strong influences on the H-2 conversion (in direct H2O2 Synthesis process) and H2O2 decomposition and/or hydrogenation reaction. While the effect of Pd oxidation state on the H2O2 formation was significant for the catalytic system containing F- and Cl- ions, the influence of the Pd oxidation state was found less important for the catalyst system containing Br- ions; the H2O2 formation selectivity increased significantly due to the presence of Br- ions, irrespective of the Pd oxidation state. The nature of the H2O2 destruction pathway (i.e. hydrogenation and/or decomposition) in the presence of hydrogen over halide-modified Pd/Al2O3 catalysts was found to be strongly dependent upon the nature of the halide ions incorporated in the catalyst during halide-modification of the catalyst. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: direct H2O2 synthesis; H2O2 decomposition; H2O2 hydrogenation; halide-modification; Pd oxidation state